2014
DOI: 10.1007/s10393-014-0918-y
|View full text |Cite
|
Sign up to set email alerts
|

Macroclimate Determines the Global Range Limit of Aedes aegypti

Abstract: Aedes aegypti is the main vector of dengue and a number of other diseases worldwide. Because of the domestic nature of this mosquito, the relative importance of macroclimate in shaping its distribution has been a controversial issue. We have captured here the worldwide macroclimatic conditions occupied by A. aegypti in the last century. We assessed the ability of this information to predict the species' observed distribution using supra-continental spatially-uncorrelated data. We further projected the distribu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
41
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(47 citation statements)
references
References 30 publications
(29 reference statements)
3
41
0
3
Order By: Relevance
“…There are reports suggesting that some of the vector borne viruses (arbovirus) such as Chikungunya, Dengue and Zika viruses are evolving them to expand their natural principal vectors (Nasci, 2014). Moreover, vector biology including their distribution is greatly under the influence of climate change (global warming) and habitat changes (Capinha et al, 2014;Khormi and Kumar, 2014). It is therefore now vital to know the extent of distribution of CHIKV vector in nature for successful vector control to reduce or stop the spread of pathogen they carry.…”
Section: Prevention and Controlmentioning
confidence: 99%
“…There are reports suggesting that some of the vector borne viruses (arbovirus) such as Chikungunya, Dengue and Zika viruses are evolving them to expand their natural principal vectors (Nasci, 2014). Moreover, vector biology including their distribution is greatly under the influence of climate change (global warming) and habitat changes (Capinha et al, 2014;Khormi and Kumar, 2014). It is therefore now vital to know the extent of distribution of CHIKV vector in nature for successful vector control to reduce or stop the spread of pathogen they carry.…”
Section: Prevention and Controlmentioning
confidence: 99%
“…14,4346 Macroclimate is another important factor in predicting the range of Aedes mosquitoes and as climate change threatens to expand the area hospitable to this species, the need for vector control efforts as well as novel vaccines and antiviral therapies for dengue and other flaviviruses will certainly grow. 47 The secondary vector, Aedes albopictus , has been implicated in previous outbreaks of dengue and chikungunya in more temperate climates, however some research has suggested that this vector species is much less efficient at transmitting the virus than Aedes aegypti , perhaps due to native Wolbachia infection. 48,49 Alternatively, recent modeling approaches have suggested that Aedes albopictus may be even more efficient than Aedes aegypti at dengue transmission, particularly when considering the longer lifespan of this species.…”
Section: Vector Description and Distributionmentioning
confidence: 99%
“…88,89 Furthermore, the Aedes aegypti vector in Mexico appears to be spreading into elevations and climes previously thought to be inhospitable. 47,89,90 Indeed, the first locally-acquired cases of dengue in Baja California state, Mexico, were reported in November, 2014 in addition to an above-average number of imported cases. 72 The socioeconomic differences that exist between Texas and Mexico that have been previously described as protective against a dengue outbreaks are likely also applicable to the cross-border situation in California, however these factors are not entirely preventative.…”
Section: Dengue and Chikungunya Risk In Californiamentioning
confidence: 99%
“…The principal vector of dengue, the invasive species A. aegypti , is distributed throughout tropical regions (Capinha et al, 2014). This vector is successful in colonising high density human populations, and often adult mosquitoes do not disperse very far, with evidence that some inhabit single households throughout their lives (Stoddard et al, 2013).…”
Section: Introductionmentioning
confidence: 99%